Posouzení úcinnosti automatického kultivacního systému pro záchyt mykobakterií BACTEC MGIT 960 ve srovnání s klasickou kultivacní metodou. Zkusenosti po jednorocním provozu - Záruba, R; Králová, M (Epidemiologie, mikrobiologie, imunologie, 2002)
The fully automatic non-radiometric cultivation system BACTEC MGIT 960 of Becton Dickinson is one of the systems using the so-called rapid metabolic method of mycobacteria cultivation. For detection of mycobacterial growth it uses the fluorescent technology. The objective of the present work is to compare the effectiveness of this system with classical cultivation on solid (egg) and liquid media. During the period from April 27, 1999 till April 28, 2000 in our department concurrently by both methods a total of 2144 samples were examined from which a total of 149 mycobacterial strains were isolated. It was revealed that the BACTEC MGIT 960 system is much more sensitive than classical cultivation (it detected 136 isolates as compared with 103 detected by the classical method): in isolation of Mycobacterium the difference in sensitivity is even more marked (from the total number of isolated strains of Mycobacterium tuberculosis the BACTEC MGIT 960 detected 105, classical cultivation only 76). The mean Time to Detection (TTD) of positive samples in the BACTEC MGIT 960 system was 13.2 days while for classical cultivation it was 33.6 days. It was thus confirmed that the BACTEC MGIT 960 achieves, as compared with classical cultivation, better results which applies to the sensitivity of the two methods as well as to the detection rate of positive samples.
Keywords: Fluorescence; spotřeba kyslíku; Culture Media; bakteriologické techniky; Oxygen Consumption; fluorescence; kultivační média; Mycobacterium; Bacteriological Techniques